Calving and reproductive performance of Angus x Hereford and Brahman x Hereford heifers fed to prebreeding target weights - D.J. Patterson; L.R. Corah; J.R. Brethour; W.R. Negus (Kansas Agricultural Experiment Station Research Reports, 1987)
The effect of heifer development on first calving and subsequent reproductive performance was evaluated in Angus x Hereford (AxH) and Brahman x Hereford (BxH) females. Heifers were fed to reach either 55% or 65% of their projected mature body weight by the start of their first breeding season. After breeding, the heifers were managed as a typical commercial range beef cow herd. Angus x Hereford heifers developed to the higher prebreeding target weights: 1) were heavier (P<.05) at calving; 2) had larger (P<.05) total precalving pelvic areas; and 3) had higher (P<.05) average postcalving body condition scores. Precalving pelvic areas were also greater (P<.05) among BxH females developed to the higher prebreeding target weight. Angus x Hereford heifers fed to the low target weight experienced 23.5% more calving problems (52.3 vs 28.8%). Only 11.3% of the BxH heifers required assistance at calving, and calving difficulty was not related to nutritional level. Postpartum interval to estrus (PPJ) was longer among low target AxH heifers, but not in BxH heifers. Calf weaning weight was not affected by heifer development; however, weights were heavier for calves raised by the BxH heifers. These data suggest that differences in weight and condition prior to first breeding persist through to the heifer's first calving and postpartum period.
Keywords: Cattlemen' s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Calving; Reproductive performance; Target weights